Docosahexaenoic acid improves cognition and hippocampal pyroptosis in rats with intrauterine growth restriction. Issue 2 (February 2023) - Wan, Lijia; He, Xiaori; He, Mingfeng; Yu, Yuanqiang; Jiang, Weiming; Liang, Can; Luo, Kaiju; Gong, Xiaoyun; Yang, Yonghui; Dong, Qingyi; Chen, Pingyang
Abstract: Background and Objective: Intrauterine growth restriction (IUGR) is defined as the failure of a fetus to reach its genetic growth potential in utero resulted by maternal, placental, fetal, and genetic factors. Previous studies have reported that IUGR is associated with a high incidence of neurological damage, although the precise causes of such damage remain unclear. We aimed to investigate whether cognitive impairment in rats with IUGR is related to pyroptosis of hippocampal neurons and determine the effect of early intervention with docosahexaenoic acid (DHA). Methods: Learning and memory function was assessed using the Morris water maze test. The morphological structure and ultrastructure of the hippocampus was examined via hematoxylin and eosin staining and electron microscopy respectively. The pyroptosis of hippocampal neuron was detected by gasdermin-D (GSDMD) immunofluorescence staining, mRNA and protein expression of nuclear localization leucine-rich-repeat protein 1 (NLRP1), caspase-1, GSDMD, and quantification of inflammatory cytokines interleukin (IL)-1β and IL-18 in the hippocampus. Results: IUGR rats exhibited decreased learning and memory function, morphological structure and ultrastructural changes in hippocampus compared to controls. IUGR rats also exhibited increased hippocampal quantification of GSDMD immunofluorescence staining, increased mRNA and protein expression of NLRP1, caspase-1, and GSDMD, and increased quantification of IL-1β and IL-18 in the hippocampus. Intervention with DHA attenuated these effects. Conclusion: Cognitive impairment in rats with IUGR may be related to pyroptosis of hippocampal neurons. Early intervention with DHA may attenuate cognitive impairment and reduce hippocampal pyroptosis in rats with IUGR.